2010
DOI: 10.1002/ddr.20378
|View full text |Cite
|
Sign up to set email alerts
|

Clavulanic acid protects neurons in pharmacological models of neurodegenerative diseases

Abstract: Clavulanic acid is a psychoactive compound with excellent blood-brain barrier permeability and safety profiles. Previous studies showed that clavulanic acid suppresses anxiety in rodents and in a primate model. In addition, clavulanic acid is thought to enhance sexual function in animal models via central nervous system (CNS) mechanisms. To further examine its potential as a CNSmodulating agent, we investigated the effects of clavulanic acid in neurotoxin-induced animal models that emulate neurodegenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Recently, it was demonstrated that clavulanic acid, at different effective dose ranges, possesses strong CNS modulating effects, including anti-anxiety effects in rodent and primate models [9], neuroprotective effects in Parkinson’s disease models in vivo [5] as well as enhanced sexual arousal in animal models through a proposed CNS-mediated mechanism [1]. These clavulanic acid-induced pharmacological activities may be due to the release of dopamine via clavulanic acid interaction with vesicle trafficking and fusion proteins Munc18-1 and Rab4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that clavulanic acid, at different effective dose ranges, possesses strong CNS modulating effects, including anti-anxiety effects in rodent and primate models [9], neuroprotective effects in Parkinson’s disease models in vivo [5] as well as enhanced sexual arousal in animal models through a proposed CNS-mediated mechanism [1]. These clavulanic acid-induced pharmacological activities may be due to the release of dopamine via clavulanic acid interaction with vesicle trafficking and fusion proteins Munc18-1 and Rab4.…”
Section: Discussionmentioning
confidence: 99%
“…Clavulanic acid decreases anxiety in rodent and primate models [9]. Further findings suggest that clavulanic acid is a neuroprotective agent in Parkinson’s models in vivo [5]. Clavulanic acid has also been shown to enhance sexual arousal in animal models, and this effect is hypothesized to be CNS-mediated [1].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, clavulanic acid protected neurons in rodents exposed to kainic acid or MPTP. Furthermore, we observed that clavulanic acid improved motor function in MPTP-treated mice in a behavioral test (Huh et al, 2010). It is believed that PD is caused by the progressive degeneration and eventual death of dopaminergic neurons of the substantianigra (SN) (Samii et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, in neurotoxin-induced animal models, clavulanic acid has been shown to improve motor function (Huh et al, 2010) suggesting that it can be neuroprotective; however, the mechanism as how clavulanic acid can induce neuroprotection is not known. We demonstrate here that clavulanic acid abrogates the effects of the neurotoxin 1-methyl-4-phenylpyridinium (MPP + ) which mimics Parkinson’s disease (PD) by inducing neurodegeneration.…”
mentioning
confidence: 99%
“…However, if the pathophysiological processes are studied, especially for the complex diseases, then models should mimic clinical settings as closely as possible, otherwise the expected results may not be achieved or the findings of such studies will be of limited value. Accordingly, comparisons between human and animal models are becoming increasingly important for both clinical and fundamental applications (Alini et al, 2008;Cox et al, 2009;Fuentes et al, 2009;Huh et al, 2010;Merchenthaler & Shughrue, 2005;Nestler & Hyman, 2010;Northoff, 2009). Among the available strategies to assess this connection, comparative systems biology has begun attracting special attention (Cox et al, 2009).…”
mentioning
confidence: 99%